1983
DOI: 10.1080/00221309.1983.9711474
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Recall of Visually Presented Additive and Nonadditive Digital Material by Deaf and Hearing Subjects

Abstract: An attempt was made to examine the encoding of visually presented additive and nonadditive digital material and its processing by deaf and hearing Ss. A 2 X 3 X 4 within-Ss design consisting of groups (45 deaf and 45 hearing Ss), numeral sets (additive, lower additive, and additive random), and recall intervals (0, 3, 9, and 12 seconds) was used. Results showed better recall of the additive set in which the third digit was the sum of the first two (e.g., 5-3-8) than other sets. Although the hearing Ss recalled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Short term recall of digits recollects all digital words in the same numerical modality of cortex. It was demonstrated that short-term recall of visually presented additive and nonadditive digital materials were performed similarly in deaf and normal subjects [27], indicating modality specificity in cortical processing. In this situation, the digital sentence manifested the same in visual cortical modality as individual digits without affected by the auditory cortex.…”
Section: A New Semantic/syntactic/episodic Model Of Language To Extenmentioning
confidence: 95%
“…Short term recall of digits recollects all digital words in the same numerical modality of cortex. It was demonstrated that short-term recall of visually presented additive and nonadditive digital materials were performed similarly in deaf and normal subjects [27], indicating modality specificity in cortical processing. In this situation, the digital sentence manifested the same in visual cortical modality as individual digits without affected by the auditory cortex.…”
Section: A New Semantic/syntactic/episodic Model Of Language To Extenmentioning
confidence: 95%
“…If visual perception testing is included as part of an LDHI assessment, it may be useful to consider the research that suggests differences in the way non-LD hearing and deaf subjects remember visually presented information (e.g., Kool, Pathak, & Singh, 1983). Other studies, however, indicate that fewer differences remain when the role of language is reduced and the examiner is able to communicate in sign language.…”
Section: Formal Assessmentmentioning
confidence: 99%